Practical challenges in following hand hygiene guidelines during the COVID-19 pandemic: an Indian perspective - Vasudevan, Jyothi; Dsouza, Madonna J.; Boratne, Abhijit V.; Bahurupi, Yogesh A. (International Journal Of Community Medicine And Public Health, 2021)
Promoting good hygiene is one of the most basic and efficient tools that all countries must continue to adopt throughout the COVID-19 pandemic. COVID-19 has spread far and wide with basically no locale left unblemished. The speed of the spread and the disturbing demise rates have seen numerous nations and wards acquaint measures with forestalling the spread of COVID‐19, and hand washing highlight firmly in these. Hand washing has gotten extensive consideration during the COVID‐19 pandemic. It is a basic, essential preventive measure that a great many people can do freely. However, in India, the specific issues hamper compelling hand washing. This article will mention to us what are the issues confronted and how we can improve in these viewpoints.